Umowa o dożywocie i służebność mieszkania - Szafrańska, Anna; Szyszka, Anna (Doctrina. Studia społeczno-polityczne, 2019)
The article deals with legal regulations of the life estate and flat easement contract as discussed in Polish law-related reference sources. The article presents the fundamental provisions, according to which the flat easement is included in the content of the right of life estate; it also defines the parties’ legal rights and obligations arising form those regulations. The performance of the flat easement as well as the ordinary use of estate is connected with expenses, encumbrances and repair costs. As these expenditures are extremely important, they are listed in detail in the article. The analysis takes into account the perspective of practicality and the resulting conclusions permit formulating the assumptions to be used while solving the existing problems or clarifying legal ambiguities concerning the institution of the flat easement and the institution of life estate contract.